1991
DOI: 10.1128/jb.173.16.4994-5009.1991
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of virC, an operon involved in the secretion of Yop proteins by Yersinia enterocolitica

Abstract: Upon incubation at 37°C in the absence of Ca2" ions, pathogenic yersiniae release large amounts of pYV plasmid-encoded proteins (PuID) or in the assembly of ifiamentous bacteriophages (gene IV product). At least the putative products of yscD, yscJ, and yscL were shown to be required for the export of Yops. YscJ turned out to be YlpB, a lipoprotein that we had detected previously. The yscM gene shares homology with yopH, the adjacent gene on the pYV plasmid. Its product does not appear to be necessary for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
268
1
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(280 citation statements)
references
References 62 publications
8
268
1
3
Order By: Relevance
“…Nevertheless, the Salmonella enterica InvF/SicA and S. flexneri MxiE/IpgC systems appear as clear variations on the same theme, despite the fact that InvF, but not MxiE, controls transcription of the operon encoding its co-activator and translocators. In pathogenic Yersinia species, a feedback regulation on transcription of yop genes by the TTS apparatus activity has been extensively studied (Michiels et al, 1991;Pettersson et al, 1996). In contrast to the Shigella and Salmonella systems, the VP-encoded TTS system of Yersinia species contains only one transcriptional activator, VirF (also a member of the AraC family) (Cornelis et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the Salmonella enterica InvF/SicA and S. flexneri MxiE/IpgC systems appear as clear variations on the same theme, despite the fact that InvF, but not MxiE, controls transcription of the operon encoding its co-activator and translocators. In pathogenic Yersinia species, a feedback regulation on transcription of yop genes by the TTS apparatus activity has been extensively studied (Michiels et al, 1991;Pettersson et al, 1996). In contrast to the Shigella and Salmonella systems, the VP-encoded TTS system of Yersinia species contains only one transcriptional activator, VirF (also a member of the AraC family) (Cornelis et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…2A). Mutational analysis (Michiels et al, 1991) has demonstrated the requirement for YscL for Yop secretion in Yersinia, but the specific function of this protein has not been elucidated. SsaL.…”
Section: Spi2 Secretion-apparatus Genes 157mentioning
confidence: 99%
“…In addition, a number of pi/Q homologues involved in protein secretion have been reported that are apparently not part of pulC-O-like operons. In the human pathogens Shigella flexneri, Yersinia enterocolitica and Yersinia pestis, homologues of PilQ are necessary for the secretion of various proteins which are significant virulence determinants (Allaoui et al, 1993;Michiels et al, 1991 ;Haddix and Straley, 1992). hrp genes encoding homologues of PilQ have been described in the plant pathogens X. campestris (hrpA 1, Fenselau et al, 1992) , Pseudomonas syringae (hrpH, Huang et al , 1992) and Pseudomonas solanacearum (hrpA , Gough et al, 1992) .…”
Section: Protein Secretionmentioning
confidence: 99%
“…solanacearum HrpA) (Michiels et al, 1991 ;Allaoui et al, 1993;Huang et al, 1992;Gough et al, 1992); and those associated with filamentous phage (M 13 protein IV, Pf3 ORF-430) (van Weezenbeek et al, 1980;Luiten et al , 1985). The remainder, which includes PiIO , Omc, HopO and ORFE (involved in competence in H. influenza e) , form a fourth group that show a high level of sequence similarity, but less obvious functional relationships .…”
Section: Outer Membrane Components (Piiq-like Proteins)mentioning
confidence: 99%